Biofilm Formation by Histoplasma capsulatum in Different Culture Media and Oxygen Atmospheres - Gonçalves, Larissa Naiara Carvalho [UNESP]; Costa-Orlandi, Caroline Barcelos [UNESP]; Bila, Níura Madalena [UNESP]; Vaso, Carolina Orlando [UNESP]; Da Silva, Rosângela Aparecida Moraes [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Taylor, Maria Lucia; Fusco-Almeida, Ana Marisa [UNESP] (Frontiers, 2020)
Histoplasma capsulatum is a dimorphic fungus that causes an important systemic mycosis called histoplasmosis. It is an infectious disease with high prevalence and morbidity that affects the general population. Recently, the ability of these fungi to form biofilms, a phenotype that can induce resistance and enhance virulence, has been described. Despite some efforts, data regarding the impact of nutrients and culture media that affect the H. capsulatum biofilm development in vitro are not yet available. This work aimed to study H. capsulatum biofilms, by checking the influence of different culture media and oxygen atmospheres in the development of these communities. The biofilm formation by two strains (EH-315 and G186A) was characterized under different culture media: [Brain and Heart Infusion (BHI), Roswell Park Memorial Institute (RPMI) with 2% glucose, Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% fetal bovine serum and nutrient medium HAM-F12 (HAM-F12) supplemented with glucose (18.2 g/L), glutamic acid (1 g/L), HEPES (6 g/L) and L-cysteine (8.4 mg/L)] and oxygen atmospheres (aerobiosis and microaerophilia), using the XTT reduction assay to quantify metabolic activities, crystal violet staining for biomass, safranin staining for the quantification of polysaccharide material and scanning electron microscopy (SEM) for the observation of topographies. Results indicated that although all culture mediums have stimulated the maturation of the communities, HAM-F12 provided the best development of biomass and polysaccharide material when compared to others. Regarding the oxygen atmospheres, both stimulated an excellent development of the communities, however in low oxygen conditions an exuberant amount of extracellular matrix was observed when compared to biofilms formed in aerobiosis, mainly in the HAM-F12 media. SEM images showed yeasts embedded by an extracellular matrix in several points, corroborating the colorimetric assays. However, biofilms formed in BHI, RPMI, and DMEM significantly induced yeast to hyphae reversal, requiring further investigation. The results obtained so far contribute to in vitro study of biofilms formed by these fungi and show that nutrition promoted by different media modifies the development of these communities. These data represent advances in the field of biofilms and contribute to future studies that can prove the role of these communities in the fungi-host interaction.
Keywords: biofilms; culture media; Histoplasma capsulatum; oxygen atmospheres; virulence factors